The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00109-013-1041-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective role for netrin-1 during diabetic nephropathy

Abstract: Recent studies implicate neuronal guidance molecules in the orchestration of inflammatory events. For example, previous studies demonstrate a functional role for netrin-1 in attenuating acute kidney injury. Here, we hypothesized a kidney-protective role for netrin-1 during chronic kidney disease, such as occurs during diabetic nephropathy. To study the role of netrin-1 during diabetic nephropathy, we induced diabetes in mice at age of 8 weeks by streptocotozin (STZ) treatment. Sixteen weeks after STZ treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
(58 reference statements)
0
30
0
Order By: Relevance
“…Rosenberger et al [38] first revealed that a hypoxia-induced increase in netrin-1 has anti-inflammatory effects exerted via an interaction with A2BAR expressed on polymorphonuclear neutrophils (polymorphonuclear leucocytes) to attenuate cytokine production and neutrophil transepithelial migration. Supporting this discovery, an anti-inflammatory effect of netrin-1 has also been observed in models of acute experimental colitis [39], acute kidney injury [40], and diabetic nephropathy [41]. Netrin-1 was robustly induced due to hypoxia in the above conditions and directly limited the trafficking of neutrophils to ameliorate inflammation through A2BAR.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Rosenberger et al [38] first revealed that a hypoxia-induced increase in netrin-1 has anti-inflammatory effects exerted via an interaction with A2BAR expressed on polymorphonuclear neutrophils (polymorphonuclear leucocytes) to attenuate cytokine production and neutrophil transepithelial migration. Supporting this discovery, an anti-inflammatory effect of netrin-1 has also been observed in models of acute experimental colitis [39], acute kidney injury [40], and diabetic nephropathy [41]. Netrin-1 was robustly induced due to hypoxia in the above conditions and directly limited the trafficking of neutrophils to ameliorate inflammation through A2BAR.…”
Section: Discussionmentioning
confidence: 89%
“…Netrin-1 was robustly induced due to hypoxia in the above conditions and directly limited the trafficking of neutrophils to ameliorate inflammation through A2BAR. In mice with partial netrin-1 deficiency, the conditions were more severe and exogenous netrin-1 alleviated the development of these diseases [39,40,41]. Meanwhile, a lack of functional A2BAR was proven to abrogate the protective effect of netrin-1 in these models, emphasizing the necessary role of A2BAR in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest a functional role for endogenous netrin-1 in attenuating diabetic renal disease. The studies of Mohamed et al [7] and Tak and colleagues [8] seem quite complimentary. "One swallow does not make a summer," but two swallows probably fly in the right direction.…”
mentioning
confidence: 93%
“…Confirmatory information from an independent source is helpful, particularly if the model is a different one and the findings are not quite the same. Tak et al [8] investigated a protective role for netrin-1 during diabetic nephropathy. They studied the role of netrin-1 during diabetic nephropathy, by inducing diabetes in mice with streptozotocin treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation